2019
DOI: 10.1080/21556660.2019.1626735
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of biosimilar infliximab (CT-P13) in a real-life setting in patients with Crohn’s disease or ulcerative colitis

Abstract: Objective: To assess the effectiveness and safety of biosimilar infliximab (CT-P13) in a real-life setting in adults with moderate-to-severe active Crohn’s disease (CD) or ulcerative colitis (UC). Methods: This multi-centre, observational cohort study was conducted at medical centres in Romania, Czech Republic, and Bulgaria. Effectiveness was measured using the Crohn’s Disease Activity Index (CDAI) for CD or partial Clinical Activity Index (pCAI) for UC. Quality-of-life (QoL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(26 reference statements)
3
7
0
Order By: Relevance
“…Recently, more studies have been published regarding the experience of patients with IBD who switched to infliximab-dyyb from RP infliximab [22][23][24][25][26][27][28][29][30][31][32][33][34]. These included one meta-analysis [22], many single group observational studies [23][24][25][26][27][28][29][30][31][32], and two studies with comparison groups [33,34]. The length of follow-up ranged from 4 months [23] to 5 years [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, more studies have been published regarding the experience of patients with IBD who switched to infliximab-dyyb from RP infliximab [22][23][24][25][26][27][28][29][30][31][32][33][34]. These included one meta-analysis [22], many single group observational studies [23][24][25][26][27][28][29][30][31][32], and two studies with comparison groups [33,34]. The length of follow-up ranged from 4 months [23] to 5 years [24].…”
Section: Introductionmentioning
confidence: 99%
“…The length of follow-up ranged from 4 months [23] to 5 years [24]. Patients with IBD were recruited from Europe [25][26][27][28][29][30][31][32][33][34] and Asia [23,24]. All except one study [34] have demonstrated no differences or noninferiority in effectiveness and safety between RP infliximab and infliximab-dyyb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 8 weeks of treatment with infliximab, significant improvements compared to placebo were seen in the physical (PCS) and mental component summaries (MCS) of the Medical Outcomes Study 36-Item Short Form Health Survey, and continued benefit was seen through week 54 [for infliximab 5 and 10 mg: PCS 6.8 and 5.9, respectively, MCS 5.9 and 6.4, respectively, placebo PCS 3.7, MCS 3.0; P < 0.01 for all comparisons). In 2019, Gheorghe published the results of a small real-life study on biosimilar infliximab in 85 patients with IBD [50] . After 30 weeks of therapy, of the 47 patients with ulcerative colitis, 55.3% showed a clinical response and 48.9% were in remission.…”
Section: Biological Therapies and Quality Of Lifementioning
confidence: 99%
“…Other studies have shown more effectiveness and tolerability in patients with UC. 63 The Peruvian Social Security (known as Es-Salud) reported biosimilarity between infliximab and CT-P13, and according to financial analysis determined it is a cost-effective decision. 64 In 2013, Park and colleagues 65 reported a Phase 1, doubleblind, parallel-group study of 22 and 30 weeks on 250 patients administered with either CT-P13 (n = 125) or infliximab (n = 125) (in two groups).…”
Section: Prospective Role Of Ct-p13 In Ibdmentioning
confidence: 99%